In situ electro-generated Ni(OH)2 synergistic with Cu cathode to promote direct ammonia oxidation to nitrogen - Xue, Yuzhou; Wang, Xuanxuan; Liu, Qing; Feng, Mengru; Ding, Zimo; Chu, Jiayue; Zhu, Wenyan; Liu, Na; Li, Zhichun (Water science and technology, 2024)
To solve the problem of low removal rate and poor N2 selectivity in direct electrochemical ammonia oxidation (EAO), commercial Ni foam and Cu foam were used as anode and cathode of the EAO system, respectively. The coupling effect between the cathode and anode promoted nitrogen cycling during the reaction process, which improved N2 selectivity of the reaction system and promoted it to achieve a high ammonia removal rate. This study showed that the thin Ni(OH)2 with oxygen vacancy formed on the surface of Ni foam anode played an effective role in the dimerization of intermediate products in ammonia oxidation to form N2. This electrochemical system was used to treat real goose wastewater containing 422.5 mg/L NH4+-N and 94.5 mg/L total organic carbon (TOC). After treatment, this electrochemical system achieved good performance with an ammonia removal rate of 87%, N2 selectivity of 77%, and TOC removal rate of 72%. Therefore, this simple and efficient system with Ni foam anode and Cu foam cathode is a promising method for treating ammonia nitrogen wastewater.